Molecular and serological surveillance of Hepatitis E virus in wild and domestic carnivores in Brandenburg, Germany. Issue 5 (14th April 2018) - Dähnert, L.; Conraths, F. J.; Reimer, N.; Groschup, M. H.; Eiden, M.
Summary: Hepatitis E virus (HEV) is a zoonotic virus which circulates in pigs and wild boars as main reservoir species. To reveal the infection rate in carnivores, we have carried out a monitoring study of raccoons, raccoon dogs, dogs and cats sampled in Brandenburg, Germany. In summary, 53.8% (43 of 80) of the raccoons, 34.3% (25 of 73) of the raccoon dogs, 56.6% (47 of 83) of dogs and 32.3% (21 of 65) of cats were tested positive for HEV‐specific antibodies. No viral RNA could be detected. This first description of anti‐HEV antibodies in raccoons and raccoon dogs worldwide and in dogs and cats in Germany highlights the natural host range expansion of HEV.